Herbal and nutrient complementary medicines for weight loss: community pharmacists' practices, attitudes, recommendations, information and education needs. (16th December 2015) - Taing, Meng-Wong; Tan, Eunice Tze Xin; Williams, Gail M; Clavarino, Alexandra M; McGuire, Treasure M
Abstract: Objectives: To investigate pharmacists' herbal/nutrient weight loss complementary medicine (WLCM) practices in the context of other pharmacist weight management support practices (provision of lifestyle advice, orlistat and meal replacement treatments); and gain insight into their attitudes, recommendations, information and education needs. Methods: Pharmacists from a randomly selected sample of 214 community pharmacies from different socioeconomic areas in the Greater Brisbane region, Australia, were invited to complete a survey to explore their weight management practices, with a specific focus on herbal/nutrient WLCM practices. Data collected from the sample group represented pharmacist practices within the metropolitan Greater Brisbane region. Key findings: This survey achieved a 51% response rate. During weight management consultations, a high proportion of customers (37%) sought advice from community pharmacists relating to WLCMs relative to other weight management practices; however, only a small proportion (10%) of pharmacists recommended them. Most were also found to be using resources that may not be evidence-based or do not provide sufficient WLCMs' information. Conclusion: Study results highlight the need for pharmacy professional bodies to develop evidence-based continuing education programmes to assist consumers with popular and widely available WLCMs products.